Impact of dispersion and intracavity polarization state on pump power fixed point in a Yb-fiber frequency comb - Shao, Xiaodong; Han, Hainian; Ma, Junyi; Zhang, Min; Wei, Zhiyi (Frontiers in Physics, 2022)
We experimentally explored the relationship between the pump power fixed point and the net-cavity dispersion in a Yb-fiber optical frequency comb. By continuously adjusting the distance of the grating pair in the Yb-fiber oscillator, we measured the pump power fixed point frequency in different dispersion regimes and different intracavity polarization states. We find that the fixed point frequency for pump power is not always near the carrier frequency but changes significantly with the net-cavity dispersion and polarization. Especially at the near zero-dispersion point, the fixed point has a local minimum, which is less than tens of THz and far lower than the carrier frequency. This is the first time to completely reveal the influence of net-cavity dispersion and intracavity polarization state on the fixed point in the experiment.